2020
DOI: 10.1186/s13075-020-02358-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 2018 and 2003 International Society of Nephrology/Renal Pathology Society classification in terms of renal prognosis in patients of lupus nephritis: a retrospective cohort study

Abstract: Background Although the 2018 revised International Society of Nephrology/Renal Pathology Society (ISN/RPS) classification was proposed recently, until now, no reports have been made comparing the association of renal prognosis between the 2018 revised ISN/RPS classification and the 2003 ISN/RPS classification. The present study aimed to assess the usefulness, especially of activity and chronicity assessment, of the 2018 revised ISN/RPS classification for lupus nephritis (LN) in terms of renal prognosis compare… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Several studies have shown that tubular atrophy and interstitial fibrosis were independent factors for poor renal evolution [ 16 – 23 ] as well as the chronicity index [ 24 ]. Tang et al [ 25 ] have developed and validated a risk score for the development of ESRD in LN, emphasizing the importance of tubulointerstitial lesions (tubular atrophy and interstitial fibrosis) than the histological subtype according to the ISN/RPS classification [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that tubular atrophy and interstitial fibrosis were independent factors for poor renal evolution [ 16 – 23 ] as well as the chronicity index [ 24 ]. Tang et al [ 25 ] have developed and validated a risk score for the development of ESRD in LN, emphasizing the importance of tubulointerstitial lesions (tubular atrophy and interstitial fibrosis) than the histological subtype according to the ISN/RPS classification [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We think it is possible that the clear distinction between the types of crescents was the reason for the increased correlation of the modified CI with outcomes. Umeda et al [34]…”
Section: Validation Studies Of the Modified National Institutes Of He...mentioning
confidence: 99%
“…We think it is possible that the clear distinction between the types of crescents was the reason for the increased correlation of the modified CI with outcomes. Umeda et al [ 34 ] also performed a retrospective comparison of the original and revised ISN/RPS classifications, including the NIH indices, at a single Japanese institution. They compared the modified NIH indices with the A, C, and A/C subclasses of the original ISN/RPS classification in terms of their correlation with a 30% decline in eGFR.…”
Section: Validation Studies Of the Modified National Institutes Of He...mentioning
confidence: 99%
“…LN was classified according to the ISN/RPS 2018 LN classification system by two experienced renal pathologists (HL and GL) who also scored the indicators independently based on the average score according to the activity index of renal tissue in lupus nephropathy (17). The intensity of immunostaining was reported by GL and blindly assessed by HL.…”
Section: Renal Histopathologymentioning
confidence: 99%